Konsep Peradaban Islam Nusantara: Kajian atas Pemikiran Syekh Ahmad Mutamakkin (1645-1740) dan KH Sahal Mahfudz (1937-2015) - Munawar Aziz (Jurnal Lektur Keagamaan, 2015)
Diskursus tentang Islam Nusantara merupakan studi strategis hubungan Islam dan politik. Islam di Timur Tengah belum bisa menerima secara utuh, namun tantangan tersebut ada pada Islam Indonesia dalam merespon demokrasi sebagai bentuk peradaban baru. Islam Nusantara merefleksikan bentuk dialog di antara nilai-nilai tersebut. Artikel ini mewacanakan bagaimana nilai-nilai budaya maupun politik menjadi sutu model hubungan Islam dan nilai-nilai tersebut secara damai. Mengacu pada kajian buku 'Arsyul Muwahiddin yang ditulis Sheikh Ahmad Mutamakkin (1645-1740) sebagai jembatan wujud hubungan antara hukum, tasawuf dan nilai-nilai budaya dalam konsep Islam. Mengacu pada buku tersebut Mutamakkin menyimpulkan bahwa konsep tentang relasi sosial dan civil society, yang disarikan dari konsep akidah, syariah dan tasawuf. Dengan demikian, Syekh Mutamakkin mengembangkan sebuah model keislaman yang komprehensif, dengan urutan yang jelas dan kongkret.Kata Kunci: Islam Nusantara, Syaria, Sufism, Arsyul Muwahiddin, Syekh Ahmad Mutamakkin The discourse on Islam Nusantara is a strategic study inside of relation Islam and politic in the international level. The problem of Arabic Country among Islam and politic is an example on this study. This is a challenge to reformulate the style of Islam which is responsive on democracy and civilizations. Islam in Indonesia (or Islam Nusantara) reflecting the concept of dialogue between Islam, politics and cultural values. This is what makes Islam Nusantara teach the values of peace and humanity. From this study, the book 'Arsyul Muwahiddin noted by Sheikh Ahmad Mutamakkin (1645-1740) on the bridge between the Islamic concept of sharia, Sufism and cultural values. The history of Syekh Ahmad Mutamakkin, in the relation with Javanese Empire, spread the views of relations among ulama, power and cultural ideas. This research, focused on several key questions: (1) how values contained in the book Sufism ‘Arsyul Muwahiddin? (2) How the Islamic identity of the archipelago, which is excerpted from the book and the history of ‘Arsyul Muwahiddin by Sheikh Ahmad Mutamakkin? The key questions that this research underlines the Islamic identity of the country, about the relationship between Islam, Sufism and local values to promote the concept of civilization in this country. Sheikh Ahmad Mutamakkin’s life history and values contained in the book ‘Arsyul Muwahiddin is a reflection to map the face of Islam Nusantara. Thus, an alternative view to contribute on Islamic model in the international sphere.Keywords: Islam Nusantara, Syaria, Sufism, Arsyul Muwahiddin, Syekh Ahmad Mutamakkin